Study of the Reasons for Sponsorship of Football in Iran (A Meta-Analytical Study) - Fahimeh Abdolhosseinlou; Mohammad Nasiri (Research in Sport Management and Marketing)
Purpose: The aim of the present study was to investigate the reasons for sponsors' support of football in Iran.Methods: The research method was meta-analysis in nature. The statistical population included all scientific sources reported regarding effective reasons for supporting investment in football in from 2012 to 2020., 11 studies that met the criteria for entering the meta-analysis were selected from the statistical population. Data analysis was performed using CMA2 and SPSS software.Results: A total of 73 factors were extracted and classified into seven main categories and entered the meta-analysis process. Economic, media and advertising and structural factors would have the highest effect size. The Cohen D index was designated as the effect size index. The result of Cochran test showed the heterogeneity in the size of the research effect; therefore, the size of the combined effect was based on the random effects model which was equal to 0.91 (a large effect size). The results of Rosenthal's Fail-safe N test, Fannel diagram, width of Egger origin and Begg and Masumdar rank correlation coefficient showed no diffusion bias error. Also, the effect size was calculated based on subgroups due to the existing heterogeneity and economic factors had the highest effect size. Conclusion: Developing clear and practical rules, using experienced sports managers and removing barriers to the presence of sponsors in football will attract more sponsors and, as a result, will lead to the development of football.